The central South America region includes Brazil, Peru, Paraguay, and Bolivia - Marengo, J. (2023)
The 2022 mean temperature for central South America was 0.23°C above the 1991–2020 average (Fig. 7.13). Much of the region had near- to above-average mean annual temperatures (Fig. 7.11). Seasonally, during December–February, much of the northern half of Brazil and some areas in northwestern Peru and southwestern Bolivia had near- to below-average temperatures. Meanwhile, the rest of region had near- to above-average conditions. During boreal autumn (March–May), most of the region experienced near- to above-average temperatures, with southern Peru and southwestern Bolivia observing below-average temperatures. Above-average temperatures also encompassed much of the region during boreal winter (June–August), with some locations experiencing mean temperature anomalies that were +2°C or higher. Parts of southern Peru continued to experience near- to below-average conditions during their winter. Below-average temperatures were observed in southern Brazil, Bolivia, and Paraguay during September–November, while the rest of the region experienced near- to above-average temperaturas. Above-average annual precipitation was observed across parts of northern and eastern Brazil, while the rest of central South America had below-average annual precipitation (Fig. 7.12). Abundant rainfall in the central and northern Amazon and drought in the southern Amazon and Parana-La Plata basin (LPB) were associated with La Niña in 2022. Below-average rainfall was dominant during the austral summer in southern Peru, eastern Bolivia, southeastern Brazil, and parts of Paraguay, suggesting an early ending to the South American Monsoon. Above-average rainfall was observed across much of eastern Brazil and southwestern Bolivia during the austral summer. During boreal autumn, below-average rainfall extended across southern Peru, Bolivia, and southern parts of Brazil. Southern Paraguay and the northern region and southern tip of Brazil had above-average autumn rainfall. Much of southern Peru, the western half of Bolivia, and parts of southern Brazil reported little to no rain during the boreal winter. Meanwhile, northern Peru, eastern Bolivia, and northeastern and southeastern Brazil had above-average rainfall during winter. Boreal spring was characterized by below-average conditions across much of the region, with central Paraguay and northeastern Brazil experiencing above-average rainfall.